MEANING AND IMPLICATIONS OF SHIRK IN LIFE EVERYDAY: A STUDY OF THE INTERPRETATION OF FI ZHILALIL QUR'AN IN THE SOCIAL CONTEXT OF BINJAI CITY COMMUNITY - Daffa Haikal; Sahdin Hasibuan (Journal Analytica Islamica, 2025)
Shirk is considered the gravest sin in Islam as explicitly prohibited in the Qur'an, for it contradicts the principle of tawhid as the fundamental foundation of faith. This study aims to explore the meaning and implications of shirk in everyday life by referring to Sayyid Qutb's Fi Zhilalil Qur'an and analyzing its relevance to the social reality of Binjai City. The research applies a descriptive qualitative method with a library research approach and thematic exegesis (tafsir maudhū'i), complemented by social observations of religious practices within the community. The findings reveal that shirk is not limited to idol worship but also encompasses the transfer of obedience and submission to authorities other than Allah in political, economic, cultural, and social domains. In Binjai City, shirk manifests in two main forms: cultural shirk, such as the use of amulets and the excessive veneration of figures, and modern shirk, including the commodification of religious symbols, superficial expressions of religiosity, and materialistic tendencies legitimized through religious narratives. The implications of shirk are wide-ranging, from spiritual crises and existential anxiety at the individual level to disintegration and social injustice at the communal level. This study underscores the need for comprehensive efforts to address shirk through tawhid-based education, contextualized da'wah strategies, and the cultivation of critical awareness regarding hidden forms of shirk. Thus, the research provides significant contributions in bridging normative Qur'anic understanding with contemporary social dynamics, particularly in fostering urban communities grounded in pure faith and social justice.